Studies on technical and economical viability of biodigesters associated to water reuse and energy cogeneration - Junior, Ederaldo Godoy; Silveira, José Luz; Giacaglia, Giorgio Eugenio Oscare (Revista Ciências Exatas, 2008)
This work evaluates technical and economical a miniETE (ministation of sewage treatment) by anaerobic-aerobic-anoxious process, associated to the utilization of biogas produced and utilization of treated effluent for fertilization and irrigation of green areas. The miniETE is modular, energy self-sufficient and constituted by the following systems: a) anaerobic, constituted by three sequential cascade anaerobic UASB digesters, with a helix shape phase separator system; b) aerobic-anoxious, constituted by a vertical cylindrical aerobic-anoxious biodigester operating with aeration of the fine bubble type; c) compact cogenerator, powered by biogas, capable of simultaneous production of electrical energy and hot water; d) effluent utilization for fertilization and irrigation, constituted by a distribution network The process aims the sanitation of sewage, utilization of produced biogas and of treated effluent, decreasing this way the environmental impact caused by the discharge without treatment of sewage in natural water courses and biogas into the atmosphere.